Diversity management: an analysis of paths, strategies and results communication (Research, Society and Development, 2022)
This article primarily aimed to analyze the diversity and inclusion management practices revealed by ten companies through their reports (specifically those of D&I), based on the contents available on the respective websites, and literature review. In achieving this purpose, specific objectives were set to capture the implementation strategies, the main challenges and obstacles of the process, as well as the definition of the scope of D&I management, based on what is understood or built in terms of doctrine. For the development of the research, the method of procedure was adopted that of survey and content analysis. It was found by this study that the strategies and paths are varied, depending on the incidence of factors such as: nature, size, size, availability and willingness of the top management to carry out, among others. The structure of the reports emphasized the occupation process (for the purpose of equalizing opportunities and representativeness), education and awareness, without specifically revealing the paths and sponsored actions.